2009
DOI: 10.1021/la9016273
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Manipulation of Aromatic Peptide Nanotubes

Abstract: Self-assembling aromatic dipeptides are among the smallest known biological materials which readily form ordered nanostructures. The simplicity of nanotube formation makes them highly desirable for a range of bionanotechnology applications. Here, we investigate the application of the atomic force microscope as a thermomechanical lithographic tool for the machining of nanotubes formed by two self-assembling aromatic peptides; diphenylalanine and dinapthylalanine. Trenches and indentations of varying depth and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 35 publications
1
23
0
1
Order By: Relevance
“…The fact that nano-crystalline regions approximately 50 nm in size were identified by LTA suggests that the effective spot size of the measurement is less than that of the remaining crater. Recent work by Sedman et al (2009) has shown features as small as 20 nm on peptide nanotubes following LTA supporting this suggestion. Fig.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The fact that nano-crystalline regions approximately 50 nm in size were identified by LTA suggests that the effective spot size of the measurement is less than that of the remaining crater. Recent work by Sedman et al (2009) has shown features as small as 20 nm on peptide nanotubes following LTA supporting this suggestion. Fig.…”
Section: Resultsmentioning
confidence: 71%
“…The typical resolution of the Wollaston wire based probes used in SThM is approximately 1 m, although the use of thinner wires (Pollock and Hammiche, 2001) or the addition of diamond tips (Brown et al, 2008) has achieved a resolution of around 100 nm. In nano-TA the conventional silicon based AFM tip is replaced by a specialised microfabricated silicon-based probe with a miniature heater that has a topographic spatial resolution of around 5 nm and a thermal property measurement resolution of up to 20 nm (Sedman et al, 2009). Importantly this probe enables a surface to be studied with the most widely applied AFM imaging mode, tapping mode, enabling the analysis of softer samples, such as polymers, without damage from the imaging probe.…”
Section: Introductionmentioning
confidence: 99%
“…Using an atomic force microscope as a thermomechanical lithographic tool, Sedman and co-workers were able to manipulate selfassembled nanotubes formed by two aromatic peptides; diphenylalanine and dinapthylalanine. Indents and trenches were thermally etched into the nanostructures, suggesting their possible use as nano-barcodes (Sedman et al, 2009). Magnetic alignment is a versatile contact-free manipulation method that is effective over the whole sample.…”
Section: Manipulationmentioning
confidence: 99%
“…In NTA the conventional silicon tip used in AFM is replaced by a microfabricated silicon-based probe with a miniature heater that has an imaging spatial resolution of around 5 nm and a thermal property measurement spatial resolution of up to 20 nm (Sedman et al, 2009). NTA can be used to map thermal properties during imaging, or to carry out local thermal analysis at defined points on a surface.…”
Section: Introductionmentioning
confidence: 99%
“…In such analysis, the probe is heated in a temperature cycle not dissimilar to DSC whilst in contact with the sample, providing quantitative information on thermally induced phase transitions. The use of a microfabricated levers to sense thermal transitions is advantageous because of their ability to measure samples down to femtograms and nanoliters rapid heating and cooling rates exceeding 100 • C s −1 , and high sensitivity to small temperature changes and heat flows (Olson et al, 2000;Sedman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%